Deep-subwavelength manipulation of waterborne acoustic waves using homogeneous membrane-type reflective metasurfaces - Jin-Chen Hsu; Herwandi Alwi; Tsung-Yen Lin; Jia-Feng Lai (AIP Advances)
In this study, a homogeneous membrane-type reflective metasurface is proposed to achieve the efficient manipulation of waterborne sounds. The metasurface is single-phase and constitutes only a stiff metal material (stainless steel); furthermore, its thickness can reach the deep-subwavelength range. Each metasurface unit is designed to comprise a cavity capped with a vibrating mass-loaded membrane. We adopt the finite-element method for the dynamic analysis of the fluid–structure interaction problem to simulate the vibroacoustic coupling fields induced by the waterborne acoustic metasurface. We demonstrate that the metasurface units can exhibit high reflectivity for waterborne sound and that vibroacoustic coupling effects are sensitive to variations in the width of the load mass. This enables phase shifts covering the entire 2π range. We reveal the working mechanisms of the membrane structure by examining the vibration modes. The examination reveals that mass–spring resonance and continuum bending vibrations cause steep phase variations in the short- and long-mass regimes, respectively. By adapting the phase profiles, we demonstrate functional manipulation by achieving anomalous reflections, retroreflections, acoustic focusing, and self-bending beams. Our results can potentially facilitate the practical application of metasurfaces in sustainable, lightweight, and high-performance waterborne acoustic devices.